Jurnal The Ability to Complete Story Problems Reviewed from Van Hiele's Theory in Problem Based Learning - Sudarsono, Ono; Awalya, Awalya; Junaedi, Iwan (Unnes Journal of Mathematics Education Research, 2021)
The purpose of this study was to find the pattern of the ability to solve geometrical story questions for fourth grade students in terms of Van Hiele's theory in the problem-based learning model. The research method used was a mixed method. The research was conducted at SDN 2 Pamulihan Cirebon. The data collection techniques used were test techniques and non-test techniques. The analysis was carried out qualitatively. The results of the study were found as follows: (a) the ability of grade IV students in solving story questions is still at the level 1 or analysis level, the students have not yet reached the level of abstraction, formal deduction, and rigor, (b) the subject of the visualization level has a pattern to identify elements. -the element that is known, but cannot mention the element in question; unable to compile mathematical models, unable to plan solving problems; (c) the analysis level subject has a pattern that can identify the known and questionable elements; be able to compile a mathematical model even though it is incomplete, be able to plan solving the problem of the story problem correctly but not systematically; can state the formulas to be used to solve the problem correctly but not systematically can answer the problem of the story correctly but the arrangement is not yet systematics.